Neither the title nor the name of the news program is available in Kurdish or Arabic on the website. X / The Reality of Structural Indicators of Kurdish Identity in the Content of Islamic Satellite Channels in the Kurdistan Region / The “Amogari” Satellite Channel as a Case Study 40 - حسن, هێمن مجيد; حمەأمين, جوان عثمان (Sulaimani Journal for Humanities, 2020)
The subject of this research is the relationship between the religious satellite channels in the Kurdistan region and the national affiliation which does not mean to the Kurdish man, except the sense of his dignity that was and still is considered his strongest shield in preserving his being, devoted to him and throughout his long history, the majority of his calls and literature spoken and written. The research aims at realizing the current reality of this social phenomenon, ie, the national affiliation, and the levels of its formative dimensions in which it settled, It aims to prepare the atmosphere for its study, evaluation and attention by other researchers in the future, especially in these days, all of which indicate us as an age of disconnection from local values. This research is also related to descriptive research, adopting the method of content analysis to address the field dimension related to the programs presented by Dr. Abdullatif entitled "Friday sermon" in the Ayamatthari satellite channel. Finally, one of the most important results is its lack of interest in the basic components of the nation and national belonging.